MENTAL IMAGE OF MEN AND WOMEN IN THE POLISH AND UKRAINIAN LANGUAGES: A COMPARATIVE ASPECT - Lazarovych, Olga; Fedynchuk, Sofiia (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2026)
The article presents a comparative analysis of the semantics of the lexemes чоловік/mężczyzna (man) and жінка/kobieta (woman) in the Ukrainian and Polish linguistic and cultural traditions, as well as the ways of forming their mental image. In both Ukrainian and Polish, this image has traditionally been based on gender roles in which a man was associated with strength, active engagement, and the role of the head of the family, while a woman was linked with emotionality, care, motherhood, and the role of the guardian of the home. However, the linguistic worldview is undergoing transformation: traditional perceptions of role models are being supplemented by modern concepts of partnership and equality. Cultural codes are shifting from patriarchal stereotypes toward a model grounded in equal rights and individual personal qualities. Consequently, the traditional (stereotypical) image of men and women is also changing. Therefore, the aim of this study is to present the results of research on a fragment of the linguistic worldview concerning the image of men and women in Polish and Ukrainian cultures, as well as to analyze their common and distinctive features in the light of contemporary gender studies. The subject of the research is the mental image of women and men in the Polish and Ukrainian linguistic worldview within two related languages. The authors employ methods of semantic and comparative analysis with elements of cognitive, structural, and descriptive approaches. The results allow us to conclude that the contemporary mental image of men and women has significantly changed compared to traditional perceptions in both Ukrainian and Polish cultures.